Hubungan Antara Indeks Massa Tubuh Dengan Jenis Hernia Inguinalis - Ringgo Alfarisi; Mizar Erianto; Fitri Chintiyani (Universitas Malahayati Lampung, 2022)
ABSTRACT: RELATIONSHIP BETWEEN BODY MASS INDEX AND TYPES OF INGUINAL HERNIA Background: One of the risk factors that can influence or increase the incidence of inguinal hernia is overweight and obesity. Body mass index (BMI) is a simple way to see the nutritional status of adults, especially with regard to underweight and overweight.Objective: To determine the relationship between Body Mass Index and the type of inguinal herniaResearch Methods: The design in this study used a cross sectional design. The population in this study were all inguinal hernia patients at Pertamina Bintang Amin Hospital Bandar Lampung in 2019-2020. The sample in this study amounted to 98 people using purposive sampling technique. Where patients with congenital hernia, chronic cough, and comorbid disease, were excluded from the study. The data obtained were analyzed using the chi square statistical test.Result: 18 respondents (20.45%) patients diagnosed with lateral inguinal hernia had normal weight and 70 respondents (79.55%) other respondents diagnosed with lateral inguinal hernia. Meanwhile, 6 respondents (60%) who were diagnosed with medial inguinal hernia were overweight-obese, while the other 4 respondents (40%) who were diagnosed with medial inguinal hernia were overweight-obese. The results of the bivariate statistical test using chi square obtained a p-value of 0.013.Conclusion: There is a significant relationship between body mass index and the type of inguinal hernia. Keywords: Body Mass Index, Lateral Inguinal Hernia, Medial Inguinal Hernia INTISARI: HUBUNGAN ANTARA INDEKS MASSA TUBUHDENGAN JENISHERNIA INGUINALIS Latar Belakang:Salah satu faktor resiko yang dapat mempengaruhi atau meningkatkan angka kejadian dari hernia inguinal adalah overweight dan obesitas. Indeks massa tubuh (IMT) merupakan cara sederhana untuk melihat status gizi orang dewasa, khususnya yang berkaitan dengan kekurangan dan kelebihan berat badan.Tujuan: Untuk mengetahui hubungan antara Indeks Massa Tubuh dengan jenis hernia inguinalisMetode Penelitian:Rancangan dalam penelitian ini menggunakan desain cross sectional. Populasi dalam penelitian ini adalah seluruh pasien hernia inguinalis sebanyak di RS Pertamina Bintang Amin Bandar Lampung tahun 2019-2020.Sampel pada penelitian ini berjumlah 98 orang dengan menggunakan tekhnikpurposive sampling. Dimana pasien dengan hernia kongenital, batuk kronis, dan penyakit komorbid, diekslusi dari penelitian. Data yang diperoleh dianalisa menggunakan uji statistic chi square.Hasil penelitian:Didapatkan 18 responden (20,45%) pasien yang didiagnosa hernia inguinalis lateralis memiliki berat badan normal dan 70 responden (79,55%) responden lainnya yang didiagnosa hernia inguinalis lateralis. Sementara itu, 6 responden (60%) responden yang didiagnosa hernia inguinalis medialis memiliki berat badan overweight-obesitas sedangkan 4 responden lainnya (40%) yang didiagnosa hernia inguinalis medialis memiliki berat badan overweight-obesitas.Hasil uji statistik bivariat menggunakan chi square diperoleh nilai p-value 0,013.Kesimpulan:Terdapat hubungan yang bermakna antara indeks massa tubuh dengan jenis hernia inguinalis. Kata kunci: Indeks Massa Tubuh, Hernia Ingunalis Lateralis, Hernia Inguinalis Medialis